2019
DOI: 10.3390/app9071460
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Reinforced Recycled Aggregate Concrete Columns under Cyclic Loadings

Abstract: Recycled concrete aggregates (RCAs) generated from construction and demolition activities have been recognized as a feasible alternative to natural aggregates (NAs). Naturally, the columns fabricated with reinforced recycled concrete (RRC) have been proposed and investigated to promote the structural use of recycled aggregate concrete (RAC). There is still, however, very limited modeling research available to reproduce, accurately and efficiently, the seismic response of RRC columns under lateral cyclic loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 67 publications
(101 reference statements)
1
10
0
Order By: Relevance
“…Prior to conducting the ML-based analysis, it is useful to identify the importance of various parameters. Such a rehearsal can provide insights into whether the selected input parameters are appropriate [ 12 , 13 ]. To achieve this objective, the powerful mathematical tool of Grey relational analysis (GRA), which has been proposed to deal with poor, incomplete, and uncertain systems [ 76 ], was used in this study.…”
Section: Parametric Importance Evaluation Using Grey Relational Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to conducting the ML-based analysis, it is useful to identify the importance of various parameters. Such a rehearsal can provide insights into whether the selected input parameters are appropriate [ 12 , 13 ]. To achieve this objective, the powerful mathematical tool of Grey relational analysis (GRA), which has been proposed to deal with poor, incomplete, and uncertain systems [ 76 ], was used in this study.…”
Section: Parametric Importance Evaluation Using Grey Relational Anmentioning
confidence: 99%
“…One of the biggest concerns is the inferior properties of RA, which would result in significant reductions in the mechanical properties of RAC [ 4 , 5 , 6 , 7 ]. This should impede the acceptance of RAC-based members, though many laboratory studies have revealed their structural feasibility [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Another wave of concern is around design and modeling, where the validity of previous code-based models and analytical procedures developed for natural aggregate concrete (NAC) components is questioned for their RAC counterparts; this issue has begun to be systematically addressed [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Wang et al [1] evaluated the performance of reinforced recycled aggregate concrete (RRC) columns under cyclic loading, using a fiber-based numerical model. With this model, they performed a comprehensive parametric study to examine the effects of a range of variables on the hysteretic characteristics of RRC columns.…”
Section: Upscaling the Use Of Recycled Aggregate Concrete In Structurmentioning
confidence: 99%
“…Many experimental investigations have been conducted on reinforced concrete columns with different CARR under uniaxial and cyclic compressive loading (Ajdukiewicz et al, 2007; Choi, 2017; Choi et al, 2012; He et al, 2017; Lei et al, 2020; Tam et al, 2014; Wang et al, 2015; Wang et al, 2019; Xiao et al, 2006, 2012; Zhang et al, 2017; Zhou et al, 2010). Zhang et al (2017) utilized 22 geopolymer/ordinary concrete specimens with different strength and demolished concrete lamps (DCL) were adopted as RCA.…”
Section: Introduction and Research Significancementioning
confidence: 99%
“…Nevertheless, a frame structure with a higher content of RCA still behaved well enough to resist an earthquake attack. Xiao et al (2012), Wang et al (2019), and Lei et al (2020) investigated the seismic behavior of columns with RCA. The results from the three studies concluded that these columns have acceptable seismic properties and they can be used in severe earthquake regions.…”
Section: Introduction and Research Significancementioning
confidence: 99%